Comparison of the long bone microstructure of two southern African marine birds, the Cape gannet (Morus capensis) and the African penguin (Spheniscus demersus) with respect to their aquatic adaptations - Dabee, Vidushi Prema (Department of Biological Sciences, 2014)
The Cape gannet (Morus capensis) and the African penguin (Spheniscus demersus) have distinct aquatic adaptations for locomotion. The gannet, which is an efficient flying bird, uses both fore- and hind limbs to propel itself under water. On the other hand, the flightless penguin swims underwater using only its forelimbs. In this study, the long bones of ten penguins and nine gannets were compared in terms of microanatomy and histology with respect to ontogenetic stage (hatchlings, juveniles and adults) and locomotion. Micronatomical and histological findings of the fore-limbs and hind limbs show that the bone microstructure of the gannets and the penguins differs significantly in term of compactness and bone remodelling. Penguin bones are more thick-walled and compact as compared to gannet bones and their cortical tissue is dominated by simple vascular canals whilst the medullary cavity is nearly absent. The forelimb bones of penguins are more compact that the hind limb bones. This is due to the aquatic adaptation of the bone to fore-limb underwater propulsion. On the other hand, the gannet bones are thin walled, less compact with primary osteons dominating the mid-cortex, and a large vacant medullary cavity is present. The gannet fore- and hind limb bones do not differ in terms of bone compactness. Ontogenetic differences in the penguin long bones show that the hatchling bears an active growth phase. Some of the bones of the juvenile penguins are still actively growing whilst the adult ones appear to have stopped growing as the bone mid-cortex is more organized. For the gannet species, the juvenile and adult differs in terms of the presence and thickness of the inner and outer circumferential layers and the presence of circumferential vascularizations. Intra-specific differences are noted in the juvenile penguins with one specimen still undergoing active growth depicted by the presence of numerous simple vascular canals. Amongst the adult penguins, one male specimen is actively molting as indicated by the presence of large resorption cavities in all of the long bones. One adult gannet individual possesses large resorption cavities in all its long bones as a result of starvation caused by perforation of its intestines. Inter-skeletal differences are noted with the stylopod and zeugopod being the most affected by sub-aquatic locomotion with osteosclerosis occurring the most in the proximal bone and decreases in the distal bones going from the pectoral to the pelvic bones in the African penguin. In the Cape gannet, the stylopod and ulna have micro-structural features for torsional resistance during flight.